Penarikan Konsep Konseling Islam Dalam Pemulihan Jiwa Dari Padangan Imam Al Ghazali - M. Fahli Zatrahadi; Darmawati Darmawati; Anisa Siti Nurjanah (AL-FIKRA, 2020)
Humans are present with all the potential that exists in them, both negative and positive, all of these potentials develop according to the direction of human life choices. Mental uneasiness originates from the development of wrong potential in humans, therefore it is necessary to take care of the soul in order to get the restoration of the soul, in this case, taking the view of Imam al-Ghazali about the restoration of the soul that starts from purification of the soul and ends in peace of mind. Islamic counseling as a solution to mental recovery in this article uses the views of Imam al-Ghazali on the concept of Sufism to obtain mental healing.